The efficacy and safety of methylprednisolone in hepatitis B virus-related acute-on-chronic liver failure: a prospective multi-center clinical trial - Lin Jia; Ran Xue; Yueke Zhu; Juan Zhao; Juan Li; Wei-Ping He; Xiao-Mei Wang; Zhong-Hui Duan; Mei-Xin Ren; Hai-Xia Liu; Hui-Chun Xing; Qing-Hua Meng (BMC Medicine, 2020)
Abstract Background Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a severe condition with high mortality due to lack of efficient therapy. Until now, the use of methylprednisolone (MP) in HBV-ACLF is still controversial. We aimed to evaluate the efficacy and safety of MP in HBV-ACLF. Methods Totally 171 HBV-ACLF patients from three medical centers were randomly allocated into MP group (83 patients treated with MP intravenously guttae for 7 days plus standard treatment: 1.5 mg/kg/day [day 1–3], 1 mg/kg/day [day 4–5], and 0.5 mg/kg/day [day 6–7]) and control group (88 patients treated with standard treatment). The primary endpoints were 6-month mortality and prognostic factors for 6-month survival. The survival time, cause of death, adverse events, liver function, and HBV DNA replication were analyzed. Results The 6-month mortality was significantly lower in MP group than control group [32.4% vs. 42.5%, P = 0.0037]. MP treatment was an independent prognostic factor for 6-month survival [HR (95% CI) 0.547(0.308–0.973); P = 0.040]. Factors associated with reduced 6-month mortality in MP group included HBV DNA and lymphocyte/monocyte ratio (LMR) (P < 0.05). Based on ROC curve, LMR+MELD had a better predictive value for prognosis of HBV-ACLF under MP treatment. No significant difference in HBV DNA replication was observed between groups (P > 0.05). Conclusions MP therapy is an effective and safe clinical strategy in HBV-ACLF, increasing the 6-month survival rate. Clinical trials registered at http://www.chictr.org.cn as ChiCTR-TRC-13003113 registered on 16 March 2013.